(untitled) (International Journal of Engineering and Computer Science, 2014)
A quintic trigonometric Bèzier curve with two shape parameters, is presented in this work. The shape of the curve can be adjusted as desired, by simply altering the value of shape parameter, without changing the control polygon. The quintic trigonometric Bèzier curve can be made close to the quintic Bèzier curve or closer to the given control polygon than the quintic Bèzier curve.